The imaginary of ‘We the peruvians’ in the traditions of Ricardo Palma - Mendívil Nina, José (2018)
The criollismo of Palma is cultural, therefore it is imaginary in us; this criollismo is a new story, which has antecedents in Pardo and Segura, but very different in its creativity and stylistic richness and which is at the same time ‘expression of a popular mestizo soul’, in which stands our human comedy with its thousand characters, “lacks truth and efficacy for social change, a change that in Traditions has a different meaning that allows us to imagine a” we “capable of denying and affirming, preserving and forgetting; to imagine their protagonism with the sense of thinking, as the exercise of a critical activity or to transform the destructive characteristic of the activity of thinking in results that are positive and profitable, generating states of perplexity.